STUDY ON MECHANICAL CHARACTERISTICS OF SCRAPER CONVEYOR UNDER CHAIN-BREAKING CONDITION - XIE Miao; YANG RunKun; LU JinNan; WU LongFei (Jixie qiangdu, 2022)
Abstact Taking into account the long-distance and heavy-duty working characteristics of the scraper conveyor, the harsh working environment and complex working conditions often lead to jams and chain broken accidents. In order to study the transient mechanical characteristics of the scraper conveyor’s stuck and broken chain, based on the elastic wave theory, the general equation of the chain longitudinal wave is established considering the resistance of the load, the boundary and initial value conditions are determined, and the mathematical model is analyzed and solved. Using MATLAB software, numerical simulation analysis was carried out on the dynamics of the scraper conveyor under the direct starting conditions and the stuck and broken chain fault conditions. Finally, combined with the virtual prototype technology, the multi-body dynamics simulation software ADAMS is used to analyze the dynamics of the scraper conveyor jam and chain broken conditions.The research results reveal the law of chain tension changes at the moment when the chain is stuck or broken.